Strategi Kiai dalam Peningkatan Kualitas Pendidikan di Madrasah untuk Menghadapi Tantangan Globalisasi - Asni Wahidah (At Tadbir: Islamic Education Management Journal, 2024)
This research aims to analyze strategies for improving the quality of education carried out by Kiai in facing the challenges of globalization at MA Al Urwatul Wutsqo. The research method used is descriptive qualitative, with data collected through observation, interviews and documentation. The research results show that the challenges of globalization include technological progress, moral decadence, and shifts in social values. The strategies implemented by Kiai to improve the quality of education to face globalization include providing adequate learning facilities, a comprehensive educational approach, selecting committed teachers, and maintaining A accreditation on an ongoing basis. This institution also focuses on developing students' character and morals through charitable activities, meeting educational standards set by the government, and integrating physical, moral, spiritual and managerial aspects in the learning process